2021
DOI: 10.13057/biodiv/d220723
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of morphological characteristics and phenetic relationship of ebony (Diospyros spp.) in Indonesia

Abstract: Abstract. Rindyaastuti R, Hapsati L, Wibowo AT. 2021. Analysis of morphological characteristics and phenetic relationship of ebony (Diospyros spp.) in Indonesia. Biodiversitas 22: 2738-2753. Diospyros L. (Ebenaceae) is an economically important genus that covers over 500 plant species. Members of this group are known to produce hard, dark, high-quality timbers known as ebony trees, while other members are known as persimmon trees. There is limited information on the morphological characters and phenetic relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…First, this study confirmed that the only ebony species in Indonesia are D. rumphii and D. celebica (Alrasyid 2002;Darmawan et al 2021). Second, D. ferrea has the widest distribution compared to the other five species of ebony (Table 2) (Alrasyid 2002;Rindyastuti et al 2021). These two things can be the basis for consideration in developing this Fancy Wood Class I species in the future.…”
Section: Ebony Distributionsupporting
confidence: 72%
See 1 more Smart Citation
“…First, this study confirmed that the only ebony species in Indonesia are D. rumphii and D. celebica (Alrasyid 2002;Darmawan et al 2021). Second, D. ferrea has the widest distribution compared to the other five species of ebony (Table 2) (Alrasyid 2002;Rindyastuti et al 2021). These two things can be the basis for consideration in developing this Fancy Wood Class I species in the future.…”
Section: Ebony Distributionsupporting
confidence: 72%
“…Particularly in Indonesia, this species was recorded in Sulawesi and Papua. Rindyastuti et al (2021) reported that this species is naturally distributed in Sulawesi. Likewise, Karlinasari et al (2020) also reported that D. celebica had been identified as having different extractive substances at growth sites in West Sulawesi, Central Sulawesi, and South Sulawesi Province.…”
Section: Ebony Distributionmentioning
confidence: 99%
“…However, Paembonan et al (2021) said that the stomatal density of D. celebica leaves in the sun-exposed area was higher than in the shaded area. In addition, many species of Diospyros were not covered by the dense trichome such as D. cauliflora, D. javanica (Rindyastuti et al 2021), and D. lanceifolia (Kalita et al 2015). Akinsulire et al (2018) investigated the taxonomic significance of epidermal and venation characters in the genus Diospyros L. (Ebenaceae) in Nigeria.…”
Section: Anatomical Comparison Among Congeneric Relativesmentioning
confidence: 99%
“…Due to their economic and ecological importance, Diospyros conservation through botanic gardens is crucial to facilitate intensive studies on their biology and prospective sustainable uses. Such studies on Diospyros have been continuously carried out at the Indonesian Botanic Gardens to support the conservation of this genus (Rindyastuti 2021;Rindyastuti et al 2021;Wanda et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the growing interest in utilizing phenotypic traits to estimate genetic variation in plants, to date, most studies conducted quantitative morphological analyses only to accompany their genetic analyses (see Jeong et al 2019;Darkwa et al 2020 for crop plants and Rindyastuti et al 2021;Qiao et al 2022 for woody species). Some biologists argue that estimating genetic diversity through morphological variation still has several limitations (Jain et al 2017) since morphological variation appears because of additive genetic variation and environments.…”
Section: Introductionmentioning
confidence: 99%